Low-cost High-performance Impedance Spectroscopy via Hardware–Software Co-design towards a CMOS Architecture - Joubert, Trudi-Heleen (University of Pretoria, 2026)
Thesis (PhD (Electronic Engineering))--University of Pretoria, 2025.